Comparing Salt Tolerance at Seedling and Germination Stages in Local Populations of Medicago ciliaris L. to Medicago intertexta L. and Medicago scutellata L - Mbarki, Sonia; Skalicky, Milan; Vachova, Pavla; Hajihashemi, Shokoofeh; Jouini, Latifa; Zivcak, Marek; Tlustos, Pavel; Brestic, Marian; Hejnak, Vaclav; Khelil, Aziza Zoghlami (Plants (Basel, Switzerland), 2020)
Salt stress is one of the most serious environmental stressors that affect productivity of salt-sensitive crops. Medicago ciliaris is an annual legume whose adaptation to agroclimatic conditions has not been well described. This study focused on the salinity tolerance of M. ciliaris genotypes compared to M. intertexta and M. scutellata in terms of plant growth, physiology, and biochemistry. Salt tolerance was determined at both germination and early seedling growth. Germination and hydroponic assays were used with exposing seeds to 0, 50, 100, 150, and 200 mM NaCl. Among seven genotypes of M. ciliaris studied, Pop1, 355, and 667, were most salt tolerant. Populations like 355 and 667 showed marked tolerance to salinity at both germination and seedling stages (TI ≤1, SI(FGP) > 0 increased FGP ≥ 20% and SI(DW) < 0 (DW decline ≤ 20%); at 100 mM); while Pop1 was the most salt tolerant one at seedling stages with (TI =1.79, SI(FGP) < 0 decline of FGP ≤ 40% and with increased DW to 79%); at 150 mM NaCl). The genotypes, 306, 773, and M. scutellata, were moderately tolerant to salt stress depending on salt concentration. Our study may be used as an efficient strategy to reveal genetic variation in response to salt stress. This approach allows selection for desirable traits, enabling more efficient applications in breeding methods to achieve stress-tolerant M. ciliaris populations.
Keywords: alfalfa; proline; salt stress; snail medick; tolerance index (TI); soluble sugar; sensitivity index (SI)